The Measurement of Fibrinolysis with Radioactive Mercury Labelled Fibrin Clots - Morse, B. S, M. D.; Nussbaum, M, M. D. (Thrombosis and Haemostasis, 1965)
A method for the preparation of standard fibrin clots labeled with radioactive mercury is described. When suspended in aqueous solutions of streptokinase, urokinase and trypsin, the release of radioactivity from the clot is proportionate to the rate of lysis. The per cent of remaining clot measured by the radioactive method and a tyrosine assay is comparable. Hg203 labelled clots are easy to prepare and may be stored for approximately 2 months.